Short and medium-term sectoral employment: Forecasting the future development of remote work - Eva Alexandri; Luca Barbieri; Daniel Seymour; Cornelia-Madalina Suta; Chris Thoung (European Trade Union Institute (ETUI), 2023)
This report provides new projections, to 2026, of remote work rates and the accompanying macroeconomic implications for the EU27, Switzerland, Iceland, Norway, Republic of North Macedonia, Turkey and the UK. Remote work covers a range of practices but few are straightforward to quantify consistently. The definition of remote work used in this report is working from home (WFH), matching the Eurostat Labour Force Survey (EU-LFS) definition. The literature review identified a range of drivers (e.g. sectoral composition of the economy) and potential outcomes (e.g. changes in expenditures on information and communications technologies (ICT)). Using a conceptual framework developed from the literature review, we modelled a baseline projection and three alternative scenarios: one that projected lower rates of WFH by 2026 compared to the baseline (Unwinding of WFH); and two that projected higher rates of WFH (Acceleration of WFH and Acceleration of WFH with contract changes). By 2026, the baseline projects that 18% of workers in the EU27, and 19.6% of workers in all 33 study countries, will be working from home. There is substantial variation in these rates by individual country, from a 2026 rate of 42% in Luxembourg to 1% in Bulgaria and Romania. Compared to the baseline, the Unwinding of WFH scenario projects nearly 350 000 fewer total workers and more than 10 million fewer WFH workers by 2026, with the reduction concentrated mostly in services. The Acceleration of WFH scenario projects more than 830 000 additional workers in total and more than 24 million more WFH workers by 2026, employed mostly in service sectors. The Acceleration of WFH with contract changes scenario projects nearly one million more total workers and more than 24 million more WFH workers by 2026. In this scenario, workers are assumed to shift from permanent to self-employed contract positions, leading to a projected increase in the rate of self-employment of 3.7 percentage points compared to the baseline. An unwinding of WFH in Europe would generate modest increases in costs for firms, mild decreases in total employment for workers and small aggregate output reductions. An acceleration of WFH, coupled with an increase in digital development in Europe, would provide benefits in terms of cost savings to firms, higher employment and higher output. However, there is a risk that higher levels of WFH could lead to contract changes that, while providing benefits to firms, could undermine workers' power, pay and benefits. This has not been explicitly modelled in these projections but warrants deeper consideration.
Keywords: 330; Telearbeit; Wirkungsanalyse; EU-Staaten; Schweiz; Island; Nordmazedonien; Türkei; Großbritannien